Does ChatGPT provide comprehensive and accurate information regarding the effects, types and programming of core exercises? - Halime Arıkan; Erkan Erol (Turkish Journal of Kinesiology)
The objective of this study is to assess the accuracy of ChatGPT's responses regarding core exercises. A total of 23 questions were asked to ChatGPT 3.5 about core exercises. Nine physiotherapists assessed the accuracy of the answers provided by ChatGPT for these questions using a 5-point Likert scale (5: strongly agree, 1: strongly disagree). The maximum possible score achievable through Likert scoring is 115, while the minimum score is 23. The answers of the artificial intelligence received an average of 3.93±0.46 (minimum: 3.48, maximum: 4.91) points. The lowest score obtained from the responses of ChatGPT was 3.22 ± 0.97 (question 21), whereas the highest score was 4.56 ± 0.53 (questions 12 and 18). Despite having some shortcomings, ChatGPT has generally provided satisfactory answers regarding core exercises. Artificial intelligence holds the potential to offer counselling to individuals, enhance their health outcomes, and support the work of professionals across the field of exercise science, including health and sports specialists.